The Potency of Photocatalytic Membrane Bioreactor for Wastewater Treatment: A Brief Review - Lathifah Puji Hastuti (Indonesian Journal of Chemical Studies, 2025)
Membrane bioreactors (MBR) are a promising method for wastewater treatment that combines microbial degradation with membrane separation. MBRs offer efficient and sustainable wastewater treatment by combining biological processes with membrane filtration, providing high-quality effluents for reuse. The advantages of MBRs, such as their compact design, reduced sludge production, and water recycling potential, make them increasingly significant in addressing global water scarcity and pollution challenges. Nevertheless, the issue of biofouling persists as a notable obstacle, primarily caused by the interplay of bacteria, membrane surfaces, and the release of extracellular polymeric substances (EPS). Integrating photocatalysts into MBR membranes offers a new method to reduce fouling. This study provides a comprehensive overview of current research on the membrane modification using photocatalysts in MBR systems, focusing on the existing challenges and prospects in this field. Despite these potential advantages, research on improving MBR membrane performance through photocatalysis is sparse. To ensure the sustainability of this technology, it is essential to consider important factors, such as reactor configuration, kinetics, fouling processes, economic feasibility, and scaling issues